2019
DOI: 10.1017/s2045796019000519
|View full text |Cite
|
Sign up to set email alerts
|

Post-SSRI sexual dysfunction & other enduring sexual dysfunctions

Abstract: Enduring sexual difficulties following treatment with selective serotonin reuptake inhibitor antidepressants have been reported to regulators since 1991, but it was only in 2006 that a formal post-SSRI sexual dysfunction syndrome was reported. The clinical, research and regulatory implications of this syndrome are considerable and researchers using epidemiological methods are well placed to map out the contours of the problem and perhaps pinpoint possible treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
6
0
7
Order By: Relevance
“…In addition, SSRI antidepressants can have negative effects on sexual function and even male fertility (Nørr et al, 2016), often even when treatment is stopped (Healy et al, 2018). They can also affect future sexual relations between men and women (Healy, 2019; Shindel, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SSRI antidepressants can have negative effects on sexual function and even male fertility (Nørr et al, 2016), often even when treatment is stopped (Healy et al, 2018). They can also affect future sexual relations between men and women (Healy, 2019; Shindel, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…35,38 Our sample included two people who suicided and who attributed their motivation to protracted withdrawal symptoms (in one case, persistent sexual dysfunction). 48,49 Affective withdrawal symptoms can be the very same symptoms for which the antidepressant was initially prescribed, implying that some patients may have confused a genuine relapse with a withdrawal syndrome. However, it has been shown that most antidepressant users can distinguish accurately between symptoms of the original disorder and adverse drug effects.…”
Section: Discussionmentioning
confidence: 99%
“…22 Afeta indivíduos de ambos os sexos, de qualquer idade ou grupo étnico, e pode surgir após uma toma única do SSRI, algumas doses de tratamento ou desenvolver-se até anos depois da exposição ao SSRI. 23 Esta entidade clínica deve ser considerada quando o doente reporta algum grau de disfunção sexual, que não estaria presente antes de iniciar o tratamento antidepressivo com SSRIs e que persiste após a remissão da depressão e da descontinuação do fármaco SSRI, tendo-se concomitantemente excluído qualquer comorbilidade que possa ser responsável por essa disfunção sexual. 22 Waldinger et al (2014) sugeriram a existência de dois subtipos de PSSD.…”
Section: Disfunção Sexual Pós-ssri 21-definição Prevalência E Classif...unclassified
“…13,18 A perturbação de excitação genital persistente não se associa ao aumento do desejo sexual nem a alterações psicológicas, podendo desenvolver-se durante o tratamento antidepressivo com SSRI ou após a sua descontinuação. 17,23 No entanto, na maioria das situações apresenta-se intimamente relacionada com a descontinuação da medicação SSRI e afeta sobretudo as mulheres, sendo mais provável a sua ocorrência durante a menopausa. 23 A síndrome dos genitais inquietos é uma perturbação genital integrada na PSSD que pode ser causada por uma neuropatia sensorial do ramo terminal do nervo pudendo e caracteriza-se por disestesias genitais e sensações genitais pré-ejaculatórias ou pré-orgásmicas, podendo associar-se também a pernas inquietas ou queixas de hiperatividade vesical, que podem persistir por tempo indeterminado após a descontinuação do SSRI.…”
Section: 2-manifestações Clínicasunclassified